Hydroxyapatite coating on Ti and Ti6A14V substrates by using electrophoretic deposition method - Albayrak, Önder. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
Electrophoretic deposition method was used to coat hydroxyapatite (HA) on titanium (Ti) and its alloy (Ti6Al4V). Main focus was elimination or decreasing the crack occurrence and increasing adhesion strength. For this purpose, chemically synthesized nano sized and naturally derived submicron sized HA powders were produced. First, these powders both in calcined and uncalcined states were deposited on Ti and Ti6Al4V substrates under different coating voltages to investigate the effect of calcination and coating voltage on coating quality. The cracks became less pronounced with decreasing applied voltage. Coatings obtained using calcined powders were seen to be free of cracks before and after sintering. Further studies were conducted to increase the adhesion strength by depositing nano-sized titanium dioxide (TiO2) powders using different coating voltages, as an inner layer between Ti6Al4V substrate and HA coating. Adhesion strength of the overall coating was found to increase with decreasing voltage used in TiO2 deposition. Furthermore, use of the TiO2 inner layer prevented HA decomposition. Finally, studies were conducted to create coating surface consisting of calcium phosphate (Ca-P) based bioceramics and TiO2. This surface was expected to combine the advantages of Ca-P (osseointegration) and TiO2 (photocatalytic bactericidal effect). TiO2 was allowed to grow from the titanium substrate to fill in the cracks in the Ca-P coating at sintering stage, and coalescence of Ca-P/TiO2 was observed.
Keywords: Titanium.; Titanium alloys.; Hydroxyapatite coating.; Electrophoretic deposition.